Production of solid fuels from regional wastes - Şentürk, Ahmet; Tosun, Yıldırım İsmail; Gündüz, Lütfullah (Makine Mühendisliği Bölümü, Karadeniz Teknik Üniversitesi, Trabzon, 1996)
Various industrial wastes such as food wastes, papers, cardboards, plastics, textiles, rubber, leather, wood, glass and metallic wastes should be recycled or be used in some industrial sectors. A certain types of wastes such as rubber, plastic, nylon andleather wastes can be recycled in their own sectors. However, some types of wastes are mainly municipal wastes and these wastes should be removed by converting them into the ash form and less harmful dirt condition should be provided by sterilisation of wastes in residential areas. Burning of these type municipal wastes and some types of organic wastes such as olive seed, tree leafs, pine corns, rose wastes or animal dirt is very beneficial to the economy of country and also protection of environment.
Keywords: solid fuel, regional waste, organic waste